Antarctic Science and Policy: Interdisciplinary Research Education (ASPIRE) - Berkman, Paul Arthur (Byrd Polar Research Center, The Ohio State University, 1997)
On the cover: "Group decision making activities and interdisciplinary approaches for Earth System Science Education." The purpose of the report is to illustrate an interdisciplinary approach for teaching Earth System Science Education (ESSE) through group decision-making activities. This educational approach has been applied successfully in an interdisciplinary capstone course on Antarctic Marine Ecology and Policy that has been taught at universities in the United States since 1982. In this course, each student becomes an "ambassador" to an Antarctic Treaty nation with the task of recommending a practical and clearly defined solution that would mitigate a specific human impact in the Antarctic marine ecosystem. These solutions are discussed and refined in working groups throughout the course to create the formal recommendations that are debated at the end of the term in a Mock Antarctic Treaty Consultative Meeting. The effectiveness of this interdisciplinary activity in teaching ESSE courses is assessed with regard to several student case studies. University Center for International Studies, Department of Zoology, School of Natural Resources and the Sidney Pressey Endowment Fund, The Ohio State University Earth System Science Education Program of the Universities Space Research Association.